Denture base resins biocompatibility testing in vivo - Kostić Milena; Najman Stevo; Mihailović Dragan; Krunić Nebojša; Gligorijević Nikola; Gligorijević Jasmina; Igić Marko; Marinković Nikola (Vojnosanitetski Pregled)
Background/Aim. The wearing of acrylic dentures is the cause of the inflammatory reaction of the oral mucosa. The aim of this study was to investigate the response of rat tissues to subcutaneous and intramuscular implantation of different acrylic samples, by histopathological analysis of the tissue. Methods. The study included two samples of hard and three samples of soft acrylic resins (heat and cold polymerized), that were subcutaneously and intramuscularly implanted in rats tissues. Implantation tests were designed to test the biological response of the surrounding tissue to the tested materials after their application for the period of two weeks and the period of four months. Results. After two weeks, regardless of the type of implantation, histopathological analysis showed an acute inflammatory response. There was an intense hyperplasia of inflammatory cells, multiplication of connective tissue as well as formation of many new blood vessels. The highest level of inflammatory changes was observed after the application of cold-polymerized resins. A lower intensity of inflammation in the case of heat polymerised resin was the result of its more complete polymerization. After the second observation period, fibrotic capsules were formed around the implanted samples indicating a chronic course of the inflammatory process. Less visible signs of inflammation and chronicity of the processes indicate that with time, i.e. with the length of the observation period, reduces inflammation. Conclusion. The subcutaneous and intramuscular implantation of acrylic resins material samples led to inflammatory response whose intensity was decreased over time. Heat polymerized resin was a biologically more acceptable in comparison to the cold polymerized acrylates.